Gustav Schmidt (ed.): A History of NATO. The First Fifty Years (Czech Journal of International Relations, 2003)
Gustav Schmidt (ed.): A History of NATO. The First Fifty Years. 1st ed. 3 volumes. Palgrave, New York 2001, ISBN 0-333-96277-X.